Phenomenology in Anthropology : A Sense of Perspective - Jackson, Michael, 1940-; Houston, Christopher; Ram, Kalpana (Book collections on Project MUSE., 2015)
This volume explores what phenomenology adds to the enterprise of anthropology, drawing on and contributing to a burgeoning field of social science research inspired by the phenomenological tradition in philosophy. Essays by leading scholars ground their discussions of theory and method in richly detailed ethnographic case studies. The contributors broaden the application of phenomenology in anthropology beyond the areas in which it has been most influential-studies of sensory perception, emotion, bodiliness, and intersubjectivity-into new areas of inquiry such as martial arts, sports, dance, music, and political discourse.